Coastal reclamation impacts to the quality of life: Tanjung Tokong, Penang - Nadzir, Nadzhirah; Ibrahim, Mansor; Mansor, Mazlina (e-International Publishing House, Ltd., UK., 2018)
The impacts of coastal reclamation to the coastal community have usually been overlooked. This paper presents the impacts of coastal reclamation on the quality of life of Tanjung Tokong’s community. The questionnaire survey data was analyzed using Statistical Package for Social Science (SPSS), and the interview was content analyzed. The results show only three variable, influenced the quality of life the most. Flash flood and traffic congestion negatively correlated with quality of life while health positively correlated with quality of life. It recommended that the coastal reclamation process should consider any temporary and permanent negative impact on the community.